Writing and space: some notes on maps and literary landscapes (XXI Century. Spanish Literature and Culture, 2020)
A literary landscape is the vital essence of the most intimate and changing map of every writer. Menchu Gutiérrez invites us to enjoy the reading of the landscape as an intelectual, emotional and sensorial experience. With old maps and echoes of memory, the mentioned writers in her article chop and change abstract landscapes, half real and half imagined, conquered through their experience and sift by the intimacy of the memories.
Keywords: landscape; memory; imagination; narrative